Antifreezing Proton Zwitterionic Hydrogel Electrolyte via Ionic Hopping and Grotthuss Transport Mechanism toward Solid Supercapacitor Working at −50 °C. Issue 27 (26th July 2022) - Sun, Weigang; Xu, Zhen; Qiao, Congde; Lv, Bingxi; Gai, Ligang; Ji, Xingxiang; Jiang, Haihui; Liu, Libin
Abstract: Hydrogel electrolyte is widely used in solid energy storage devices because of its high ionic conductivity, environmental friendliness, and non‐leakage property. However, hydrogel electrolyte is not resistant to freezing. Here, a high proton conductive zwitterionic hydrogel electrolyte with super conductivity of 1.51 mS cm –1 at −50 °C is fabricated by random copolymerization of acrylamide and zwitterionic monomer in the presence of 1 m H2 SO4 and ethylene glycol (EG). The antifreezing performance and low temperature conductivity are ascribed to hydrogen bonds and ionic bonds between the components and water molecules in the system and can be tuned by changing the monomer ratio and EG contents. The proton hopping migration on the ionic group of the polymer chains and Grotthuss proton transport mechanism are responsible for the high proton conductivity while Grotthuss transport is dominated at the glassy state of the polymer chains. The electrolyte‐assembled supercapacitor (SC) offers high specific capacitance of 93.5 F g –1 at 25 °C and 62.0 F g –1 at −50 °C with a capacitance retention of 91.1% and 81.5% after 10 000 cycles, respectively. The SC can even work at −70 °C. The electrolyte outperforms most reported antifreezing hydrogel electrolytes and has high potential in low‐temperature devices. Abstract : A serial of proton antifreezing hydrogel electrolytes are fabricated. An extreme low‐temperature conductivity of 1.51 mS cm –1 at −50 °C is obtained. The proton transfer is facilitated by hopping on the zwitterionic group and Grotthuss proton conductivity mechanism. The electrolyte‐assembled supercapacitor demonstrates good electrochemical performance at low temperature of −50 °C.